Spätzle Homolog-Mediated Toll-Like Pathway Regulates Innate Immune Responses to Maintain the Homeostasis of Gut Microbiota in the Red Palm Weevil, Rhynchophorus ferrugineus Olivier (Coleoptera: Dryophthoridae) - Muhammad, Abrar; Habineza, Prosper; Wang, Xinghong; Xiao, Rong; Ji, Tianliang; Hou, Youming; Shi, Zhanghong (Frontiers in Microbiology, 2020)
Spätzle (Spz) is a dimeric ligand that responds to the Gram-positive bacterial or fungal infection by binding Toll receptors to induce the secretion of antimicrobial peptides. However, whether the Toll-like signaling pathway mediates the innate immunity of Rhynchophorus ferrugineus to modulate the homeostasis of gut microbiota has not been determined. In this study, we found that a Spätzle homolog, RfSpätzle, is a secretory protein comprising a signal peptide and a conservative Spz domain. RT-qPCR analysis revealed that RfSpätzle was significantly induced to be expressed in the fat body and gut by the systemic and oral infection with pathogenic microbes. The expression levels of two antimicrobial peptide genes, RfColeoptericin and RfCecropin, were downregulated significantly by RfSpätzle knockdown, indicating that their secretion is under the regulation of the RfSpätzle-mediated signaling pathway. After being challenged by pathogenic microbes, the cumulative mortality rate of RfSpätzle-silenced individuals was drastically increased as compared to that of the controls. Further analysis indicated that these larvae possessed the diminished antibacterial activity. Moreover, RfSpätzle knockdown altered the relative abundance of gut bacteria at the phylum and family levels. Taken together, these findings suggest that RfSpätzle is involved in RPW immunity to confer protection and maintain the homeostasis of gut microbiota by mediating the production of antimicrobial peptides.